Nocturnal Coleoptera and Hemiptera Diversity at Giam Siak Kecil Bukit Batu Biosphere Reserve Indonesia - Hasni Ruslan; Imran S. L. Tobing (UIN Sunan Gunung Djati Bandung, 2021)
Giam Siak Kecil Bukit Batu is a biosphere reserve which one of its functions is as a habitat for wildlife. However, biodiversity data in the Giam Siak Kecil Bukit Batu Biosphere Reserve (GSKBB-BR) is still very minimal, including insects (Coleoptera and Hemiptera). This research was conducted to determine the diversity of Coleoptera and Hemiptera in the GSKBB Biosphere Reserve, Riau, Indonesia. The research was carried out using an exploratory method using